Re-examining the demand for money in ASEAN-5 countries - Abdullah, Hussin; Ali, Jamal; Matahir, Hylmee (Canadian Center of Science and Education, 2010)
The objective of this study is to re-examine the demand for money in ASEAN-5 countries, namely Indonesia, Malaysia, the Philippines, Singapore, and Thailand using the autoregressive distributed lag (ARDL) approach to cointegration analysis. The empirical results show that there is a unique cointegrated and stable long-run relationship among broad monetary aggregate, income, interest rate, exchange rate, foreign interest rate, and inflation. We found that the income elasticity and the exchange rate coefficient are positive while the inflation elasticity is negative. This indicates that depreciation of domestic currency increases the demand for money, supporting the wealth effect argument and people prefer to substitute physical assets for money balances that support our theoretical expectation.